β-Chemokines and neutralizing antibody titers correlate with sterilizing immunity generated in HIV-1 vaccinated macaques - Heeney, Jonathan L. (The National Academy of Sciences, 1998)
One of the obstacles to AIDS vaccine development is the variability of HIV-1 within individuals and within infected populations, enabling viral escape from highly specific vaccine induced immune responses. An understanding of the different immune mechanisms capable of inhibiting HIV infection may be of benefit in the eventual design of vaccines effective against HIV-1 variants. To study this we first compared the immune responses induced in Rhesus monkeys by using two different immunization strategies based on the same vaccine strain of HIV-1. We then utilized a chimeric simian/HIV that expressed the envelope of a dual tropic HIV-1 escape variant isolated from a later time point from the same patient from which the vaccine strain was isolated. Upon challenge, one vaccine group was completely protected from infection, whereas all of the other vaccinees and controls became infected. Protected macaques developed highest titers of heterologous neutralizing antibodies, and consistently elevated HIV-1-specific T helper responses. Furthermore, only protected animals had markedly increased concentrations of RANTES, macrophage inflammatory proteins 1α and 1β produced by circulating CD8(+) T cells. These results suggest that vaccine strategies that induce multiple effector mechanisms in concert with β-chemokines may be desired in the generation of protective immune responses by HIV-1 vaccines.